Ukuran Perusahaan sebagai Moderator Pengaruh Dividen dan Kinerja terhadap Nilai di Sektor Konsumsi - Hermawan, Imam Tri; Purwanti, Meilani (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the effect of dividend policy and financial performance on firm value, with firm size as a moderating variable. The study subjects included primary consumer goods companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. The independent variables were Dividend Payout Ratio (DPR), Return on Equity (ROE), Current Ratio (CR), Total Asset Turnover (TATO), and Debt to Equity Ratio (DER), while Price to Book Value (PBV) was used as a proxy for firm value. Firm size (SIZE) was used as a moderating variable using panel data regression analysis and a moderation interaction approach. The results showed that DPR had a significant positive effect on PBV, while ROE had a significant negative effect on PBV. Meanwhile, CR, TATO, and DER did not significantly influence PBV. Firm size had a significant positive effect on PBV. Regarding moderation, firm size significantly moderated the effect of DPR and DER on PBV, indicating that in larger companies, the positive effect of DPR and DER on firm value tends to weaken. The interaction of company size with ROE, CR, and TATO did not show a significant moderating effect.